DESIGNING SUSTAINABLE ARCHITECTURE AND IRRIGATION SYSTEMS TAKING INTO ACCOUNT CLIMATE CONDITIONS (International journal of artificial intelligence, 2025)
This article analyzes the principles of designing sustainable architecture and irrigation systems taking into account climatic conditions. Maintaining ecological balance, increasing energy efficiency and rational use of water resources are of great importance when designing buildings and structures in hot and dry regions. The study studies the effectiveness of using solar energy, rainwater harvesting systems and water-saving irrigation technologies. At the same time, the importance of combining traditional and modern architectural styles is also highlighted.